Study the Results of Treatment of Patients with Lung Abscess Using Modern Endobronchoscopy (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
New technologies in the diagnosis and treatment of purulent-inflammatory lung diseases have made it possible to slightly reduce the incidence over the past decades, which is confirmed by existing literature publications, but the search for the most effective and low-traumatic treatment options is extremely relevant. Among the minimally invasive methods of treating purulent lung diseases, in our opinion, treatment methods using endobronchial sanitation and catheterization of purulent cavities are of no small importance. We set ourselves the task of developing the optimal method of treating purulent lung diseases, using minimally invasive methods and maximum efficiency. For this purpose, we preferred to use the positive properties nasotracheobronchial purulent catheterization.